The effect of video games on the life style of adolescents (of adolescents of the second district 5 tehran) - Bakhshizadeh, Simin; Jafari, Ali (The Turkish Online Journal of Design Art and Communication, 2016)
The aim of this study was investigating effect of video games on change of life style of adolescence in the second grade of high schools in district 5 of Tehran. Methodology f this research is applied according to purpose and correlative-surveying according to method. Statistical population of this research is 28348 students in district 5 of Tehran high schools that sample volume was determined 384 by Cochran formula and sample was selected by simple random method and stratified sampling method. Results showed that the highest effect of life style among studied variables is first in apparent coverage (β=0.31), second in fashions (β=0.27), third spending leisure time (β= 0.16), and the fourth imitation and modeling (β=0.13). The results showed that the second term school district 5 Tehran lifestyle of adolescents’ function of dependent variables, or cover appearance, fashion-oriented, leisure time activities and duplication of video games is modeling. Because the two variables influence social relationships and family relationships were eliminated from the equation of video games was not fixed.
Keywords: Computer Games; Lifestyle; Youth; Cover Appearance; Fashion-Oriented; Bilgisayar Oyunları; Yaşam Tarzı; Gençlik; Kapak Görünümü; Moda Odaklı